Optimal design and planning of biodiesel supply chain with land competition - Andersen, Federico Ezequiel (2012)
In this work we propose an MILP multiperiod formulation for the optimal design and planning of the Argentinean biodiesel supply chain, considering land competition and alternative raw materials. The country is divided into twenty three regions, each one including existing crops, oil and biodiesel plants and potential ones. The model includes intermediate and final products, i.e., seed, flour, pellets and expellers, oil, pure and blending biodiesel and glycerol. Crop fields, storage and production plants, as well as distribution centers for internal and external markets are also represented. We consider the possibility of sowing energetic crops, such as Jatropha curcas, in marginal areas. The time horizon is of seven years, divided into 84 periods. The mathematical model has been implemented in GAMS providing a powerful decision-making tool that can be applied to other regions or countries by adjusting specific data.